Clinical utility of double-balloon enteroscopy in suspected Crohn's disease: a single-centre experience. Issue 7 (July 2016) - Tun, Gloria S.Z.; Rattehalli, Deepa; Sanders, David S.; McAlindon, Mark E.; Drew, Kaye; Sidhu, Reena
Abstract : Background: Small bowel Crohn's disease has a heterogeneous presentation leading to a delay in diagnosis. Capsule endoscopy is now a well-established diagnostic tool; however, few studies have evaluated the role of double-balloon enteroscopy (DBE) in patients with suspected Crohn's disease. Histology obtained at DBE is useful in addition to clinical symptoms, blood parameters and capsule endoscopy findings to aid diagnosis and further management. Objective: The aim of this study was to evaluate the impact of DBE and histology on the management of patients with suspected small bowel Crohn's disease. Methods: DBE procedures including histology for suspected Crohn's disease from 2006 to 2014 were retrospectively reviewed. Follow-up data for all patients were collected. Results: In our series of 399 double-balloon enteroscopies, 122 procedures were performed in 100 patients for suspected Crohn's disease. Positive DBE findings were found in 60% of patients. Forty-five per cent of patients were treated as Crohn's disease on the basis of a combination of histology, endoscopic appearance, clinical symptoms and blood parameters. Histology was diagnostic of Crohn's disease in 8% and supportive of it in 15%. In 12%, an alternative diagnosis was made, of whom two patients were diagnosed with small bowel malignancy on histology. After a median follow-up period of 27 months, the actual prevalence for a new diagnosis of Crohn's disease in our study was 38%. Conclusion: DBE has a useful place in clarifying the diagnosis in patients with suspected Crohn's disease. Although histology can be nondiagnostic, the combination of the macroscopic appearance with clinical correlation is useful in the diagnosis and management.